Surgical Premaxillary Setback with Vomerine Ostectomy for Complicated Bilateral Cleft Lip - Yuzuka Oda; Yosuke Ojima; Nanako Ayabe; Maya Aoyagi; Yukiko Ida; Hajime Matsumura (Journal of Plastic and Reconstructive Surgery, 2024)
Important factors that affect the initial repair of complete bilateral cleft lip (CBCL) include not only the width of the cleft but also the distance between the premaxilla and alveolar bone. We report a case of a patient with CBCL in whom favorable morphological and aesthetical results were achieved by surgical premaxillary setback. The patient was a 5-month-old boy with CBCL, who had a severely protruding premaxilla. Despite repeated lip adhesion before lip closure surgery, wound dehiscence occurred, and therefore, we performed premaxillary setback with vomerine ostectomy. The bone was removed posterior to the vomero-premaxillary suture, and the premaxilla was indirectly stabilized by bilateral mucosal bridging. The procedure for the vomer worked well, and his premaxilla was moved back enough to undergo surgery. The premaxillary setback is thought to be a reasonable option to treat CBCL in patients with a protruding premaxilla. The subsequent long-term follow-up of the midfacial development of these patients is necessary.